A Comparative Study of the Protection of Children's Image Rights in Cyberspace - Maryam Ghanizadebafghi; Fateme Chaji (پژوهشهای حقوقی)
Advances in technology and advancing in the digital age and cyberspace have led to the emergence of new rights for individuals. One of the new issues is the right of children to be photographed in cyberspace; where children - as one of the most vulnerable sections of society - are exposed to all kinds of victimization through the violation of their rights. In this regard, it is necessary to protect children and make protective laws due to being in an unequal situation. Dissemination of children's images due to persistence in cyberspace causes much harm to children. Invasion of privacy, affecting their right to self-determination, sexual abuse of images, violation of the right to mental health and psychological damage are among the effects of abusing children's image rights; which are all against his interests. The present study seeks to provide legal solutions by examining the importance of the status of this right and its violations and by using descriptive-analytical method and comparative approach. Findings indicate that the systematization of cyberspace along with the close supervision of governments requires performance guarantees in case of violation; This vacancy is clearly visible in the domestic legal system of Iran.